Structure to utilize interventionists' implementation experiences of a family-based behavioral weight management program to enhance the dissemination of the standardized intervention: The TODAY study. (August 2017) - Chadwick, Jennifer Q; Van Buren, Dorothy J; Morales, Elisa; Timpson, Alexandra; Abrams, Ericka L; Syme, Amy; Preske, Jeff; Mireles, Gerardo; Anderson, Barbara; Grover, Nisha; Laffel, Lori
Background: For a 2- to 6-year period, interventionists for the TODAY (Treatment Options for type 2 Diabetes in Adolescents and Youth) randomized clinical trial delivered a family-based, behavioral weight-loss program (the TODAY Lifestyle Program) to 234 youth with type 2 diabetes. Interventionists held at least a bachelor's degree in psychology, social work, education, or health-related field and had experience working with children and families, especially from diverse ethnic and socioeconomic backgrounds. This article describes the administrative and organizational structure of the lifestyle program and how the structure facilitated collaboration among study leadership and lifestyle interventionists on the tailoring of the program to best suit the needs of the trial's diverse patient population. Methods: During the pilot phase and throughout the duration of the trial, the interventionists' experiences in delivering the intervention were collected in a variety of ways including membership on study committees, survey responses, session audio recordings, and feedback during in-person trainings. Results: The experiences of interventionists conveyed to study leadership through these channels resulted in decisions to tailor the lifestyle intervention's delivery location and ways to supplement the standardized educational materials to better address the needs of a diverse patient population. Conclusion: The methods used within the TODAY study to encourage and utilize interventionists' experiences while implementing the lifestyle program may be useful to the design of future multi-site, clinical trials seeking to tailor behavioral interventions in a standardized, and culturally and developmentally sensitive manner.